Murottal Qur'an on Anxiety and Sleep Quality of Patients Undergoing Dialysis: Scoping Review - Putro, Dimas Utomo Hanggoro; Setiawan, Arifin; Wibowo, Arif Apriyanto; Sucipto, Muhamad Bayu; Fesanrey, Rian Andito; Sugandi, Veri (Poltekkes Kemenkes Jakarta III, 2024)
Chronic kidney failure is a non-communicable disease problem that causes global problems. Patients with chronic kidney failure require dialysis therapy, one of which is hemodialysis. Chronic kidney failure patients undergoing hemodialysis may experience anxiety, depression, and decreased sleep quality. The purpose of this study was to determine the effect of murottal Al-Qur'an therapy on anxiety, depression, and quality of sleep in chronic kidney failure patients undergoing hemodialysis. The method used is scoping review with the Google Scholar database and Springer Link. The keywords used are Chronic Kidney Disease Patients